Chinese Herbal Medicines Facilitate the Control of Chemotherapy-Induced Side Effects in Colorectal Cancer: Progress and Perspective - Chen, Dongmei; Zhao, Jun; Cong, Weihong (Frontiers in Pharmacology, 2018)
Side effects, including nausea, vomiting, mucositis, peripheral neuropathy and diarrhea, have been frequently reported in colorectal cancer (CRC) patients undergoing chemotherapy. Chinese Herbal Medicines (CHMs) display distinct clinical outcomes, as a result, they have been increasingly used as an adjuvant therapy to manage chemotherapy-induced side effects. In this review, we aim to intensively explore the molecular mechanisms of CHMs, underline the significance of CHMs in mitigating the side effects induced by chemotherapy, and examine the necessary studies required to understand the role of CHMs in alleviating chemotherapy-induced side effects. Specifically, ginger, Astragali Radix and Liujunzi Decoction have been verified to ameliorateimprove some common chemotherapy-related side effects, including ameliorating nausea and vomiting by strengthening immunocyte function and reducing serotonin levels. Banxia Xiexin Decoction and Huangqin Decoction have been confirmed to be beneficial to chemotherapy-induced mucositis and irinotecan-induced delayed-onset of diarrhea, which achieved through suppressing certain enzymes involved in irinotecan metabolism and prostaglandin E2 synthesis. Moreover, Niuche Shenqi Wan, Guilong Tongluo Decoction, Huangqi Guizhi Wuwu Decoction, and curcumin tumeric have been found to display potential therapeutic effects for preventing the genesis and development of peripheral neurotoxicity induced by chemotherapy. These findings have further emphasized the pivotal role of CHMs in improving the outcomes of chemotherapy-induced side effects in CRC. Nonetheless, more molecular evidence is required to comprehensively understand and more appropriately apply CHMs in routine clinical practice for CRC.